A new Orient : from German scholarship to Middle Eastern studies in Israel - Levy, Amit (Brandeis University Press, 2024)
"This study seeks to examine the history of Zionist academic Orientalism in light of its German-Jewish background as a history of knowledge transfer stretching along an axis from Germany to Palestine"-- Provided by publisher.
Text in English, the original language is undetermined.
Keywords: Universiṭah ha-ʻIvrit bi-Yerushalayim. -- Makhon le-limude Asyah ṿe-Afriḳah.; Orientalism -- Study and teaching -- Israel -- History -- 20th century.; Orientalism -- Study and teaching -- Germany -- History -- 20th century.; Middle East -- Study and teaching -- Israel -- History -- 20th century.; Middle East -- Study and teaching -- Germany -- History -- 20th century.; Orientalisme -- Étude et enseignement -- Israël -- Histoire -- 20e siècle.; Orientalisme -- Étude et enseignement -- Allemagne -- Histoire -- 20e siècle.; Moyen-Orient -- Étude et enseignement -- Israël -- Histoire -- 20e siècle.; Moyen-Orient -- Étude et enseignement -- Allemagne -- Histoire -- 20e siècle.; HISTORY / Europe / Germany.; HISTORY / Jewish.; HISTORY / General